Yksilöllisiä valintoja ja kielitaustan vaikutusta – henkilöviitteiset hän-, he-, se- ja ne-pronominit kielielämäkertahaastatteluissa - Lappalainen Hanna; Priiki Katri (Suomen soveltavan kielitieteen yhdistys AFinLA ry, 2025)
The article examines variation in the use of the third-person pronouns hän and he (standard forms for human references) vs. se and ne (standard forms for non-human references) when referring to people in the interviews collected during the project “A Hundred Finnish Linguistic Life Stories” in 2017–2018. The focus is on two age groups, born in the 1950s and 1990s, and the data includes 32 interviews of people from different social and regional backgrounds. Eight of the interviewees spoke Finnish as their second language. The data is examined both quantitatively (with statistical methods) and qualitatively. The results show that there is considerable variation between individual speakers. Speakers with higher education born in the 1950s were the only relatively homogenous group in the data: they consistently preferred hän and he in the interviews when referring to human subjects. In the younger age group, being an L2 speaker appeared to be one of the factors affecting pronoun choices.